Pharmacists' Approach to Optimise Safe Medication Use in Paediatric Patients - Nicole Keuler; Annatjie Bouwer; Renier Coetzee (MDPI AG, 2021)
Paediatric patients are unique, yet challenging patients to care for by pharmacists. Paediatric medicine use requires special consideration. Pharmacists play an important role in educating and counselling patients, carers, and healthcare workers. Further, pharmacists have the necessary knowledge and skills to optimise safe medicine use in paediatric patients. This article provides basic principles for safe practices in paediatric medicine by following the nine rights of medication administration.